Restoration of fluid and electrolyte balance after exercise - Shirreffs, S. M. (Canadian Journal of Applied Physiology, 2001)
Post-exercise restoration of fluid balance after sweat-induced hypohydration avoids the detrimental effects of a body water deficit on physiological function and subsequent exercise performance. For effective restoration of fluid balance, the consumption of a volume of fluid in excess of the sweat loss and replacement of electrolyte, particularly sodium, losses are essential. Intravenous fluid replacement after exercise has been investigated to a lesser extent and its role for fluid replacement in the dehydrated but otherwise well athlete remains equivocal.